Impact of World Oil Prices on the Value of Kazakhstani Companies - Akanayeva, Tolkyn; Tishtykbayeva, Arnagul (Journal of Finance and Financial Law, 2021)
The article examines the impact of world oil prices on the value of Kazakh companies based on their own calculations. The subject of the analysis is the shares of companies from various sectors of the economy. The purpose of this article is to study the impact of world oil prices on the stock prices of selected companies in Kazakhstan. The results of the study show that the market value of the companies studied is highly dependent on changes in world oil prices on world exchanges.